Structural insights into the effect of cholinium-based ionic liquids on the critical micellization temperature of aqueous triblock copolymers - Khan, Imran
Symmetrical poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (PEG-PPG-PEG) triblock copolymer with 82.5% PEG as the hydrophilic end blocks, and PPG as the hydrophobic middle block, was chosen to study the effect of ionic liquids (ILs) on the critical micellization temperature (CMT) of block copolymers in aqueous solution. In the present work, cholinium-based ILs were chosen to explore the effect of the anions on the copolymer CMT using fluorescence spectroscopy, dynamic light scattering (DLS), viscosity (Z), FT-IR spectroscopy, nuclear magnetic resonance (NMR), and direct visualization of the various self-assembled nanostructures by scanning electron microscopy (SEM). The result suggests that ILs have the ability to decrease the CMT of the aqueous copolymer solution which is dependent on the nature of the anions of the ILs. The present study reveals that the hydrophobic part PPG of the copolymer has more influence on this behavior than the PEG hydrophilic part.